The mediating role of student satisfaction between quality management principles of ISO 9001:2008 and communication behavior in higher education - Mohd. Noor Azizaman, Nur Mazreen (Medwell Journals, 2016)
ISO 9001:2008 is a customer-oriented quality management system and in higher education institutions (HEIs), it is designed to ensure quality of teaching and learning process delivered to students. In a highly competitive higher education market, Student Satisfaction (SS) and positive Communication Behavior (CB) among students are important to sustain loyalty of students towards the HEIs. Public universities in Malaysia are concerned about ensuring quality of higher education services and ISO 9001:2008 is adopted to manage quality of teaching and learning process. Recent trend in Malaysia's public HEIs highlighted that determining students' CB, satisfaction and the practice of Quality Management Principle (QMP) of ISO 9001:2008 are crucial for the public universities to sustain their performances in term of getting higher quality rating, higher enrollment of students, loyalty of the students towards the HEIs and securing compliance to the accreditation bodies. Most previous studies on quality of higher education addressed the effectiveness of ISO QMP from the service provider perspective and research assessing the QMP and its effect on SS and CB from the service receiver perspective is less emphasized. This issue led to the important of studying how the QMP is linked to the SS and CB in higher education setting as well as the mediating role of SS between the QMP and CB. The conceptual model of this study features four constructs of QMP, students' perceived outcome of the teaching and learning performance to determine SS and word of mouth of services marketing literature to measure positive CB. Using stratified random sampling procedure, a questionnaire was distributed to final year students of ISO certified faculties in a public university. Hierarchical regression analysis performed on the 351 completed questionnaires revealed that there are significant correlations between variables of this study in the first three regression models. In regression four, that is when SS and CB were controlled, the mediating effect of SS between the QMP and CB was observed in higher education setting. This study highlights the need to give greater focus on SS as mediator for improving positive CB to spread out favorable image of public universities in domestic and global higher education markets.